2021
DOI: 10.1016/j.virol.2020.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Development and utilization of an infectious clone for porcine deltacoronavirus strain USA/IL/2014/026

Abstract: We report the generation of a full-length infectious cDNA clone for porcine deltacoronavirus strain USA/IL/2014/026. Similar to the parental strain, the infectious clone virus (icPDCoV) replicated efficiently in cell culture and caused mild clinical symptoms in piglets. To investigate putative viral interferon (IFN) antagonists, we generated two mutant viruses: a nonstructural protein 15 mutant virus that encodes a catalytically-inactive endoribonuclease (icEnUmut), and an accessory gene NS6-deletion virus in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Recent studies have reported the construction of several reverse genetics systems for PDCoV via a T7-based system and a BAC-based system [ 38 , 39 ]. In contrast, combined with a one-step homologous recombination, we used the BAC-based system to more rapidly establish a reverse genetics system for PDCoV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have reported the construction of several reverse genetics systems for PDCoV via a T7-based system and a BAC-based system [ 38 , 39 ]. In contrast, combined with a one-step homologous recombination, we used the BAC-based system to more rapidly establish a reverse genetics system for PDCoV.…”
Section: Discussionmentioning
confidence: 99%
“…To establish a rapid and sensitive anti-PDCoV drug screening platform, a Nluc gene with many preponderant features, including small size, stability, and higher bioluminescence activity was designed to replace the NS6 gene due to its nonessential requirement for normal viral replication [ 38 ]. Recombinant PDCoV expressing Nluc was constructed on the basis of CRISPR/Cas9 technology, as described previously [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PDCoV NS6 interacts with RIG-I/MDA5, which in turn interferes with the binding of RIG-I/MDA5 to double-stranded RNA (dsRNA), resulting in the reduction of RLR-mediated IFN-β production ( 79 ). Whereas, Deng et al removed NS6 from the infectious clone of PDCoV and found that the deletion of NS6 did not affect the ability of the infectious clone virus to inhibit the type I IFN responses, implying that NS6 does not act as an IFN antagonist during PDCoV infection ( 80 ). PDCoV NS7a competes with tumor necrosis factor receptor-associated factor 3 (TRAF3) and IRF3 for binding to IκB kinase ε (IKKε) by interacting with the kinase domain and the scaffold dimerization domain of IKKε simultaneously, forming an antagonistic effect on RLR-mediated IFN-β production ( 81 ).…”
Section: Pathogenesis Of Pdcovmentioning
confidence: 99%
“…The emerging coronavirus could cause widespread transmission among humans and animals, posing a major threat to human health and causing significant economic losses to the global livestock and trade industries. To date, at least six coronaviruses have been found to be pathogenic to pigs, They include porcine epidemic diarrhea virus (PEDV), porcine transmissible gastroenteritis virus (TGEV) and porcine acute diarrhea syndrome coronavirus (SADS-CoV), porcine respiratory coronavirus (PRCV), porcine transmissible gastroenteritis virus (TGEV), porcine haemagglutinative encephalomyelitis virus (PHEV) and porcine deltacoronavirus (PDCoV) [ 16 ]. Among them, as PDCoV is a newly emerged enteric pathogenic coronavirus that can cause severe diarrhea of piglets [ 3 ] in recent years, few studies have been conducted [ 17 ].…”
Section: Discussionmentioning
confidence: 99%